Kajian terhadap penggunaan perisian dan perkakasan multimedia di kalangan guru dalam P & P di sekolah menengah zon Skudai - Abu Bakar, Roslina (2009)
This study is conducted to determine of using multimedia software and hardware among teachers in the process of teaching and learning and to look the usage of PBK at secondary school in Zone of Skudai. The population of the respondent were 1028 teachers from 12 school in Zone of Skudai. The sample of this study were 202 teachers. This is quantitative research using 70 item questionnaire. Descriptive statistic analysis will be used and the finding are presented by using mod, percentage and mean. The data were collected by using the Statistical Package For The Social Science (SPSS). The trusted of the questionnaire were alpha=0.940. Overall of this analysis was shown that teachers at secondary school in zone of Skudai using PBK in teaching and learning and they always used Microsoft Office software and the hardware, example: computer, LCD and television. The result in this study will shown that the respondent was not expert to use the high technology of software and hardware.